Development of point-of-care testing devices to improve clozapine prescribing habits and patient outcomes - Kalaria SN (Dove Medical Press, 2019)
Shamir N Kalaria,1 Deanna L Kelly21Center for Translational Medicine, University of Maryland School of Pharmacy, Baltimore, MD, USA; 2Department of Psychiatry, School of Medicine, Maryland Psychiatric Research Center, University of Maryland School of Medicine, Baltimore, MD, USACorrespondence: Deanna L KellyMaryland Psychiatric Research Center (MPRC), 55 Wade Avenue, Catonsville 21228, MD, USATel +1 410 402 6861Email dlkelly@som.umaryland.eduAbstract: Although clozapine has demonstrated superior efficacy in patients with schizophrenia and other serious mental health illness, drug utilization rates are significantly low due to safety concerns and administration challenges. Previous research indicates that current barriers to clozapine use include lack of confidence and knowledge by prescriber, therapeutic monitoring requirements, lack of support and infrastructure to for adequate monitoring and patient adherence, and inadequate understanding of clozapine’s benefit-risk profile by policy makers and payers. One potential solution to optimizing clozapine therapy and improving clinical outcomes is the use of point-of-care testing (POCT) devices. Although the drug development process for currently used therapeutics is widely acknowledged, little is known regarding the development of POCT devices by the clinical community. The aim of this review is to provide a summary of the regulatory approval process and current availability of POCT devices for monitoring clozapine therapeutics. The potential role of POCT devices in clinical trials to inform personalized dosing strategies and improve patient outcomes will also be discussed.Keywords: clozapine, schizophrenia, patient outcomes, point-of-care testing devices, regulatory, therapeutic drug monitoring